Apoptotic cell: linkage of inflammation and wound healing - Wu, Yu-Sheng; Chen, Shiu-Nan (Frontiers in Pharmacology, 2014)
We consider that from the wound to the healing process, the physiology point key to linkage of the process is still unclear. The process from inflammation to the wound healing is divided into three phase: 1. inflammation process, 2. tissue formation, and 3. tissue remodeling. The inflammation program including cell produced related factors and immune cells infiltration. We thought the inflammation factors that may be also involved in the followed healing process. But the question is “what kind of factor is the major key involved in the end of the inflammation then to initiate the healing”. We suspect that the apoptosis of immune cell may be the major key to end of inflammation and to initiate the healing.